PORTOFOLIO OPTIMAL MODEL MARKOWITZ SAHAM IDX ESG LEADERS DALAM TERANG LAUDATO SI’ - Florian Indra Kusuma Irawan; I Putu Sugiartha Sanjaya (KRISNA: Kumpulan Riset Akuntansi, 2025)
This study examines the formation of an optimal portfolio using stocks from the IDX ESG Leaders Index through the Markowitz Model approach, integrated with the principles of Integral Ecology from the encyclical Laudato Si’. The background of this research is the pressing issue of environmental degradation, including climate change, deforestation, illegal, unreported, unregulated (IUU) fishing, air pollution, and water crises in Indonesia. Pope Francis in the encyclical Laudato Si’ emphasizes the importance of incorporating environmental aspects into economic decision-making. This study utilizes data from 30 companies within the IDX ESG Leaders Index, which meet environmental, social, and governance (ESG) criteria. The advantage of this research lies in its holistic approach that considers not only financial factors but also environmental and social impacts, in line with the principles of Integral Ecology of Laudato Si’. Portfolio evaluation is conducted using three performance measures: Sharpe Ratio, Treynor Ratio, and Jensen Ratio. The research results show that the optimal portfolio of IDX ESG Leaders can be formed from BBRI (45%), MAPI (35%), TBIG (15%), and PWON (5%). This portfolio yields a return of 11.18% with a risk of 3.55% per six months. This portfolio is better than JKSE which only provides a return of 3.43% with a risk level of 5.29%. Based on Sharpe, Treynor, and Jensen Index measurements, this portfolio outperforms the two other portfolios also formed from IDX ESG Leaders stocks. This study contributes to the development of Financial Management theory and Divine Philosophy related to sustainable economics, provides practical guidance for investors, and serves as an evaluation material for the Indonesia Stock Exchange policies.